Compression, expansion, or dynamic equilibrium? The evolution of health expectancy in New Zealand. Issue 8 (13th July 2004) - Graham, Patrick; Blakely, Tony; Davis, Peter; Sporle, Andrew; Pearce, Neil
Abstract : Study objective: To evaluate the New Zealand evidence for three theories of population health change: compression of morbidity, expansion of morbidity, and dynamic equilibrium. Design: Using the Sullivan method, repeated cross sectional survey information on functional limitation prevalence was combined with population mortality data and census information on the utilisation of institutional care to produce health expectancy indices for 1981 and 1996. Setting: The adult population of New Zealand in 1981 and 1996. Participants: 6891 respondents to the 1981 social indicators survey; 8262 respondents to the 1996 household disability survey. Main results: As a proportion of overall life expectancy at age 15 the expectation of non-institutionalised mobility limitations increased from 3.5% to 6% for men, and from 4.5% to 8% for women; the expectation of agility limitation increased from 3% to 7.5% for men and from 4.5% to 8.5% for women, and the expectation of self care limitations increased from 2.0% to 4.5% for men and from 3.0% to 6.0% for women. These changes were primarily attributable to increases in the expectation of moderate functional limitation. Conclusion: The dynamic equilibrium scenario provides the best fit to current New Zealand evidence on changes in population health. Although an aging population is likely to lead to an increase in demand for disability support services, the fiscal impact of this increase may be partially offset by a shift from major to moderate limitations, with a consequential reduction in the average levels of support required.